ePALS: Utilizing ICT to promote English Language Learning for Young Learners through Global Connection - Nadea Velenti Puspa; Devinta Puspita Ratri; Urifah Urifah (EDUCAFL : Journal of Education of English as Foreign Language, 2022)
The proper use of digital learning technologies in the classroom may boost student engagement, assist teachers in improving lesson ideas, enable individualized learning, and also assists learners in developing 21st-century abilities. ePals is one of global online learning platforms that can be used for connecting, communicating and collaborating with teachers and students all over the world. ePals is utilized to teach English that provides opportunities to English learners including young learners to communicate with people across countries. Descriptive qualitative method was used to acquire the data gained from observation and interview. The findings revealed that the use of ePals for young learners becomes effective teaching and learning process to connect with students all over the world as a media to use the target language. Young learners were enthusiastic about activities of the project made by the teacher with school partners through ePals that allow young learners to communicate with foreigners using English, even though there were some problems encountered by the teacher and young learners about the internet connection and language. Hence, with the success to bring the experience of using the target language for young learners, the use of ePals with different levels is highly suggested.